The contributions of performance management systems to performance in the Namibian context. - Hamumokola, Ndafuda Ndayandjoshisho (My University, 2014)
Although there is considerable interest in the role of performance management systems (PMS) to enhance innovation and performance, there is limited literature regarding successful implementation in organisations. Most research has focused on the technicalities of performance management implementations, while neglecting the human reactions that influence the outcomes of such systems. This research therefore aimed to examine employees’ perceptions of performance management systems in various organisations and how performance management systems, or the lack thereof, specifically influence performance in the Namibian organisational context. A multiple case study methodology was adopted for the research, where open-ended questionnaires and semi-structured interviews were used to collect data from various organisations. Data was primarily analysed by means of qualitative content analysis which was supported by the pattern matching technique. The research findings supported goal setting theory which predicts that performance benefits can be realised by implementing specific challenging goals because they have a motivational effect on employees compared to vague and easy goals. Findings also supported theory which suggests employee participation in goal setting and providing feedback led to higher performance compared to when goals are assigned and no feedback is given. The findings supported predicted positive relationships between rewards and performance. However, findings also suggested that performance management systems, or lack thereof, are unfair because rewards are distributed unjustly, which has a negative effect on performance. Nevertheless, it was suggested that employees are more motivated to perform by intrinsic factors, including achieving challenging goals, than extrinsic factors. These findings not only supported goal setting theory, they supported McGregor’s (1960) theory Y which argued that employees are ambitious and motivated by more than money, yet surprisingly also supported his theory X as it was revealed that some employees would only work harder if rewards, or performance bonuses, are given. Although the research aimed to test goal setting theory, findings also supported Vroom’s (1964) valence-instrumentality-expectancy theory, Maslow’s (1943) and McClelland’s (1975) need theories, which all argue that performance is enhanced by other sources of motivation. The findings supported contradictory theories, yet discovered interdependency among the theories, which created a cyclical notion. This means, Vroom’s (1964) theory argues that an employee can be motivated to perform better when there is a belief that the better performance will lead to good performance appraisal and in the realisation of personal goal in the form of some reward. It, however, implies that goal setting theory has no impact on employees’ performance. Yet, according to the qualitative findings, some employees will only increase performance if their performance is monitored and appraised. Therefore organisations are required to have performance management systems in place, in turn, supporting goal setting theory. The research attempted to generate meaningful insight that would be beneficial to organisations, in and outside Namibia, that are considering implementing or improving their performance management systems by incorporating what employees perceive to be fundamentally important. Communication, management support, performance feedback, education and training, goal setting and employee participation are amongst the factors perceived as essential to effective performance management systems implementation. As literature (Bernardin & Beatty, 1984; Fox & Spector, 2002) has affirmed, these findings stress that the effectiveness of performance management systems depends on employees’ attitudes and perceptions of the systems.
Keywords: Performance management; Performance management systems; Employee perceptions; Goal setting theory